RESULTS AND SOCIAL EFFECTIVENESS ANALYSIS OF THE USE OF PROPERTY OBJECTS OF UKRAINE - Zyuz D.V. (Pressing Problems of Public Administration, 2018)
The effectiveness of the use of property objects in the context of economic and social changes isanalyzed. It is substantiated that the transformational processes that were implemented in the socioeconomiclife of the country led to a deep recession and a constant decline in production capacity.Recommendations have been developed that should promote economic growth in the medium andlong term, more ef cient use of property and serve to gradually improve social standards of living.